4-Pentenoic acid exhibits broad-spectrum antibacterial activity against foodborne pathogens by disrupting bacterial membrane integrity and inhibiting efflux pump systems - Jiaming Mu; Jie Li; Fushuang Duan; Rui Wen; Xuepeng Cai; Qingling Meng; Jun Qiao; Zhongmei Ma (International Journal of Food Microbiology, 2026)

Boron-mediated pectin demethylesterification improves Na+ retention in root cell wall and alleviates salt stress in Brassica napus L. - Yu Yang; Wenjing Hao; Rui Jing; Xiaolei Feng; Diqing Yin; Muhammad Riaz; Mu Lu; Yusheng Niu; Lei Yan (Plant Science, 2026)

Integrating optical remote sensing and airborne gamma for lithological classification using an artificial neural network: A case study in Wuliji, North China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Geochronology and Geochemistry of Cretaceous volcanic rocks in the Central Lhasa Block, China: Constraints on the evolution of the Neo-Tethys Ocean - Zhi-Qiang Kang; Rui Wang; Chun-Xi Shan; Ji-Feng Xu; Feng Yang; Sheng-Liang Pei; Ji-Zhong Mu; Ling-Ling Wu; Lu Zhou (Journal of Asian Earth Sciences, 2026)

Upcycling hazardous electric arc furnace dust into defect-rich ZnO/ZnFe2O4 heterojunction for in situ H2O2 electrogeneration and water purification - Lijuan Jia; Bo Liu; Guoxing Mu; Yiqiang Ji; Fang Wang; Rui Cao; Ping Ning; Shuo Cui; Jiayu Feng (Chemical Engineering Journal, 2026)

Pyrethrin II impairs mitochondrial potential through ROS and MAPK pathways in HT‑22 cells - Jiaojiao Gao; Xinbi Zhang; Qie Mu; Yurong Liu; Hong Yang; Rui Cao; Xiuwei Wang; Baofeng Yu; Li Zhang; Yaoyao Guo (NeuroToxicology, 2026)

Response of juvenile black rockfish (Sebastes schlegelii) to water temperature: Growth, antioxidant capacity, and metabolism - Xinting Mu; Qing Li; Zhiqiang Zhang; Xiaoqian Cheng; He Ma; Tomoaki Itayama; Rui Han; Yinghai Wu (Aquaculture International, 2026)

Imidazole-based dual-function molecular structure for a cross-cycle-resistant, long-cycle, membrane-free, anode-free zinc-based battery - Zhenhe Chang; Rui Mu; Wei Zhang; Chaoyue Zhang; Ziang Yao; Haotong Wang; Baohui Wang; Hongjun Wu; Di Gu (Chemical Engineering Journal, 2026)

All-in-one transparent radiative cooler: Integrating daylighting, passive cooling, and triboelectric power generation for energy-saving buildings - Yuxuan Gu; Rui Chen; Yageng Bai; Fengyu Wen; Yashu He; Jierun Ma; Haoyuan Tan; Yifan Wang; Pengbo Lian; Haikun Zhu; Jianxin Mu (Chemical Engineering Journal, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Innovations in arid land salinization management: Xinjiang's evolving paradigm for saline-alkali land governance - Jiandong Yu; Jihong Zhang; Zhenhua Wang; Li Guo; Jinzhu Zhang; Zhengjiang Feng; Yue Wen; Rui Chen; Xiaoguo Mu (Journal of Cleaner Production, 2026)

Transition conditions between seepage-induced and buoyancy-induced reservoir landslides: Insights from sensitivity analysis on reservoir landslide stability - Zongxing Zou; Yikai Niu; Luoxia Li; Rui Mu; Liangqing Wang; Haojie Duan (Engineering Geology, 2026)

An intelligent lithofacies identification method for tight carbonate reservoirs integrating dynamic clustering and BiLSTM-attention network - Guangjie Fu; Zihao Mu; Haiwei Mu; Rui Yang; Meiqi Jia; Xinyu Li (Earth Science Informatics, 2026)

Optimizing water use and biodiversity outcomes in soybean–maize strip intercropping systems - Zhendong Liu; Xiudi Shangguan; Huaiyu Mu; Jiahao Zhou; Linyao Li; Shishuo Li; Rui Zong; Xianghao Hou; Yanli Fan; Mingming Zhang; Quanqi Li (Agricultural Systems, 2026)

Exposure to second-generation flame retardants and risk of metabolic diseases: a systematic review and meta-analysis - Li Shi; Wei Du; Xi-Yuan Peng; Juan Miao; Wei Li; Attiq Ur-Rehman; Meng-Wei Ge; Lu-Ting Shen; Rui Feng; Kang Zhong; Zhi-Ren Mu; Hong-Lin Chen (Archives of Toxicology, 2026)

CoTiO3 immobilized on nickel foam for degradation of levofloxacin via peroxymonosulfate activation: Electron transfer pathways and degradation mechanism - Zhonghua Mu; Peng Cui; Rui Gao; Jikai Liu; Wei Li; Yushu Zhang; Wenqiang Ma; Hairui Li; Shiqi Wu; Shuzheng Zhang; Zhaohui Wang; Lei Yang; et al. (Process Safety and Environmental Protection, 2026)

Combinatorial PPTase screening and systematic metabolic engineering for high-level indigoidine production in Corynebacterium glutamicum - Jiali Zhang; Zeyu Li; Rui Lu; Junsong Xiao; Yingying Zhu; Wei Xu; Wanmeng Mu (Food Bioscience, 2026)

Sustainable and selective gold extraction from electronic waste using conjugated microporous polymer aerogels - Wei Liu; Zhaoqi Zhu; Xicheng Liu; Mengqi Zhao; Rui Jiao; Peng Mu; Hanxue Sun; An Li (Chemical Engineering Journal, 2026)

Simultaneous remediation of heavy metals in mining soil using nZVI-supported attapulgite - Jun Ren; Caili Tong; Hanru Ren; Ming Gao; Gui Ma; Yunmeng Li; Rui Zhu; Xuri Mu; Chun Yang; Ling Tao (Environmental Geochemistry and Health, 2026)

High-value utilization of hazardous solid waste for efficient electrocatalytic oxygen reduction to produce hydrogen peroxide - Bo Liu; Xiaoshuang Song; Guoxin Mu; Jiayu Feng; Fang Wang; Rui Cao; Zibin Pan; Feixiang Lu; Ping Ning; Shuo Cui; Lijuan Jia (Environmental Research, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

A non-destructive Ammonia-based pork freshness detection method utilizing UV-DOAS and spectral reconstruction fitting neural network - Yufei Ju; Rui Zhu; Mu Li; Xuan Wang; Xijun Wu; Yungang Zhang (Food Chemistry, 2026)

Climatological characterisation and trends of extreme winds and their application to power transmission lines in China - Hongyu Wang; Cong Jiang; Feifei Mu; Kai Liu; Rui Mao; Xin Yin (Natural Hazards, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Immobilization mechanism of Ca(H2PO4)2-modified attapulgite on multiple heavy metals in mining soils: Speciation changes, risk assessment and ecotoxicity - Jun Ren; Rui Zhu; Hanru Ren; Ling Tao; Xuri Mu (Science of The Total Environment, 2026)

Corrigendum to “Real-time cooperative multi-target tracking with low-cost radar in complex marine environments” [Ocean Eng. 345 (2026) 123694] - Fei Wang; Qingwang Han; Mu Lv; Rui Gao (Ocean Engineering, 2026)

Real-time cooperative multi-target tracking with low-cost radar in complex marine environments - Fei Wang; Qingwang Han; Mu Lv; Rui Gao (Ocean Engineering, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Combinatorial engineering of 2-C-methyl-D-erythritol 4-phosphate pathway flux optimization and key enzymes spatial organization for (−)-α-bisabolol production in Escherichia coli - Junsong Xiao; Zeyu Li; Roulin Chen; Rui Lu; Jiali Zhang; Yingying Zhu; Wanmeng Mu (Food Bioscience, 2026)

Pathway optimization and membrane engineering for highly efficient production of indigoidine in engineered Escherichia coli - Zeyu Li; Rui Lu; Heng Hu; Roulin Chen; Dingjie Zhou; Yingying Zhu; Wanmeng Mu (Bioresource Technology, 2026)

The research on combustion performance of dual-cycle chain combustion furnace - Zhenhao Gu; Xiaoying Liu; Linjie Wu; Rui Mu; Haopeng Wang (Bioresource Technology, 2026)

Comprehensive assessment of secondary metabolite diversity and in vitro anti-diabetic properties in Sanghuangporus quercicola cultured under different conditions - Mingxing Yu; Na Zhang; Xiaofeng Ma; Xiaoshuang Zhou; Shude Yang; Weihang Peng; Yin Li; Yuejun Mu; Xianhao Cheng; Rui Zhang; Yongfei Ming (Systems Microbiology and Biomanufacturing, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Phaeovulum Molybdatiresistens sp. nov., a Molybdate-resistant Bacterium Isolated from Eutrophic Pond Water - Jianjun Song; Yuanshuo Qiu; Ke Ma; Yuelin Liu; Jia Wang; Yaqi Liu; Xiaolong Song; Kaiyue Wang; Jinhua Hu; Weidong Mu; Yanfang Zhao; Aijv Liu; et al. (Current Microbiology, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Iron-doped biocarriers enhanced nitrogen removal from saline wastewater in an unplanted constructed wetland-microbial electrolytic cell system - Longqiang Yi; Changyuan Liu; Xinyu Rong; Kexin Li; Ruina Zhang; Xin Su; Xinting Mu; Li Wan; Yinghai Wu; Rui Han (Journal of Environmental Management, 2025)

PMTFIM: Integrating machine learning with nutrient balance theory to estimate multi-stage paddy fertilization information at field scale over large regions - Housheng Wang; Xiang Gao; Wei Jiang; Xuerong Lang; Xian Hu; Meihua Qiu; Qiankun Guo; Yonghong Liang; Xuelei Wang; Yue Mu; Rui Ren; Ganghua Li; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Dual identification optical sensor for sodium benzoate and potassium sorbate based on UV-DAS combined with SEP-CNN-TL - Junfeng Wang; Rui Zhu; Jie Gao; Fei Xie; Mu Li; Changyin Li; Yungang Zhang; Hongbin Lin (Food Control, 2025)

Understanding the inhibition effect of hemicellulosic sugars on the enzymatic hydrolysis of cellulose: A combined experimental and computational study - Xiaoxiao Jiang; Tan Lai Heng; Yuguang Mu; Rui Zhai; Mingjie Jin (Bioresource Technology, 2025)

Exploration of the resistance mechanism of Botrytis cinerea to pyrimethanil - Liting Wu; Hongjiao Mu; Rui Xiao; Zhiqiu Qi; Rujun Zhou (Journal of Plant Diseases and Protection, 2025)

Phosphorus speciation, controlling factors, and ecological risk assessment in lagoon sediments: a case study of the Shamei Lagoon, Qionghai, Hainan - Kun Yuan; Xuan Mu; Guangning Xiao; Kexin Li; Wantong Zhou; Rui Wang; Shisheng Wang (Frontiers in Marine Science, 2025)
The Shamei Lagoon in Qionghai, Hainan, is an ecologically significant coastal wetland system that has recently faced increasing ecological risks due to phosphorus (P) pollution. In this study, 22 sediment samples were systematically collected from the main lagoon body, river inlets, and the transitional zone to the open sea. A comprehensive approach incorporating standardized phosphorus fractionation, spatial interpolation, redundancy analysis, and ecological risk assessment was used to investigate P speciation, spatial distribution patterns, controlling factors, and ecological risks. The results showed that: (1) Total phosphorus (TP) concentrations ranged from 261.87 to 875.74 mg/kg, with a mean of 415.72 mg/kg, comparable to typical lagoons in China. Inorganic phosphorus (IP) dominated the P fractions (mean: 317.70 mg/kg), with Fe/Al-bound phosphorus (Fe/Al-P, mean: 183.52 mg/kg) markedly exceeding Ca-bound phosphorus (Ca-P, mean: 105.88 mg/kg). Organic phosphorus (OP) had the lowest contribution (mean: 98.02 mg/kg). (2) The primary sources of P pollution were agricultural runoff and aquaculture waste, industrial discharges and vessel leakage, and regional calcareous deposition. High TP and OP concentrations were concentrated in the southwest river inlet zone, directly linked to fertilizer runoff and tourism-related wastewater. IP levels were elevated in the southern region, driven by hydrodynamic processes. Fe/Al-P was enriched in the central lagoon, likely associated with oil degradation from vessels. Secondary peaks of Ca-P occurred in the southwest aquaculture zone and the northeastern mangrove area, attributed to feed residues and shell debris, respectively. (3) Cation exchange capacity (CEC) was identified as the primary controlling factor for spatial variation in P speciation (explained variance: 46.0%, p < 0.01), followed by organic matter (OM), while pH exhibited a marked negative regulatory effect. (4) At 45.5% of sampling sites, TP levels exceeded the ecological safety threshold (600 mg/kg), and 18 sites, mainly located near the river mouth and central lagoon, were classified as heavily polluted, posing a threat to aquatic ecological security. These findings indicate that sediment P pollution in the Shamei Lagoon is driven by multiple anthropogenic activities. Mitigation strategies should prioritize control of agricultural non-point sources, aquaculture residues, and vessel oil pollution, along with sediment remediation focused on enhancing CEC.

Skeleton engineering of conjugated microporous polymer for highly efficient PM capture in harsh environments - Cailin Guo; Wei Liu; Mengxue Li; Peng Mu; Anli Yi; Zhaoqi Zhu; Rui Jiao; Hanxue Sun; An Li (Journal of Hazardous Materials, 2025)

Remediation mechanism of KH2PO4 modified attapulgite on mining soil contaminated by heavy metals - Jun Ren; Xuri Mu; Hanru Ren; Ling Tao; Rui Zhu (Journal of Environmental Chemical Engineering, 2025)

Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Zhaocheng Liu; Rui Zhang; Yi Zhang; Huijun Mu; Xinyi Jiang; Jian Zou; Tingting Wang; Ying Yin (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

PEEK-derived composite film combines high thermal conductivity and excellent joule heating properties for smart thermal management electronic sensing floors - Yageng Bai; Long Xie; Haicheng Ren; Xueling Cao; Wenchong Zhang; Fengyu Wen; Yashu He; Jierun Ma; Lin Cheng; Yifan Wang; Haoyuan Tan; Yuxuan Gu; et al. (Chemical Engineering Journal, 2025)

Using Interactive Multi-Media Panorama Virtual Reality to Balance Heritage Science, Education and Conservation At Zhoukoudian, Fangshan UNESCO Global Geopark - Jun-Ting Qiu; Tong-Yu Zhang; Lixian Tian; Xin-Min Rui; Hong-Xu Mu; Liang Qiu; Long-Xin Xu (Geoheritage, 2025)

CAFM: a freeware for geochemical data processing and concentration–area fractal modeling and its application for identifying uranium anomalies of different genesis - Jun-Ting Qiu; Jiang-Kun Li; Hong-Xu Mu; Xin-Min Rui; Yun-Han Yang; Liang Qiu (Applied Geochemistry, 2025)

Identifying the Alkaline Tolerance-Related Genes Through Transcriptome Analysis of Halomonas alkalicola CICC 11012 s - Lei Zhai; Shuaicheng Mu; Ruina Liu; Rui Liu; Geer Lin; Qi Han; Su Yao (Current Microbiology, 2025)

Potential Impacts of the North Atlantic Horseshoe Pattern on China Compound Heat‐Humidity Extremes - Jiayi Mu; Qianrong Ma; Shiquan Wan; Rui Hu; Shujuan Hu; Guolin Feng (International Journal of Climatology, 2025)
Compound heat‐humidity extremes (CHHEs) have gained significant attention as crucial indicators of heat stress. This research investigates the summer wet bulb globe temperature (WBGT) to elucidate the spatial variation of CHHEs across China from 1961 to 2022. The results reveal a clear increase in CHHEs, with the highest WBGT observed in southeastern China, while significant increases are noted in the northwestern and northeastern regions. Empirical orthogonal function analysis identifies three leading patterns: a consistent spatial increase, a north (decreasing)–south (increasing) dipole, and a west (decreasing)–east (increasing) dipole. Both observations and model simulations indicate that the North Atlantic Horseshoe (NAH) sea surface temperature (SST) anomaly pattern is a reliable predictor for CHHEs in China via influencing the North Atlantic Oscillation (NAO) and modulating large‐scale circulations. This combined with the westward extension of the Western North Pacific Anomalous Anticyclone (WNPAC), leads to a consistent rise in CHHEs, particularly in Central China. Regarding the north–south dipole, air‐sea interactions driven by the NAH reinforce the negative phase of the Eurasian (EU) teleconnection pattern through the NAO, intensifying cyclonic and anticyclonic anomalies over Mongolia to northern China and southern China, respectively. Furthermore, the NAH pattern during May–July effectively predicts summer CHHEs north–south dipole variations using the genetic algorithm‐based evolving neural network. This research offers valuable insights for predicting CHHEs in China from the perspective of North Atlantic SST anomalies.

Enhancing regional-scale simulation accuracy of paddy runoff by coupling water balance models with remote sensing - Housheng Wang; Rui Ren; Xiang Gao; Huazhan Zhang; Wei Jiang; Xuerong Lang; Xian Hu; Xiaosan Jiang; Kun Zhao; Bin Zhang; Zhipeng Liu; Wenjuan Zheng; et al. (Journal of Hydrology, 2025)

Ag nanowires boost graphene aerogel as anode for charge-transfer in nonclassical electroactive microbial fuel cells - Bo Yan; Yingzhu Guo; Shujian Cheng; Liangding Dou; Yun Yang; Xiaoxiao Guo; Yangbo Chen; Weiwei Cai; Yufeng Zhang; Zhe Liu; Zhaohui Meng; Rui Mu; et al. (Fuel, 2025)

Development of cascade nanoreactors by fusing bone-targeting engineered extracellular vesicles to modulate bone microenvironment for treatment of diabetic osteoporosis - He Yi; Fang Depeng; Chen Xiang; Shen Hongdou; Shao Xiaoyan; Lin Jiaquan; Liu Na; Shen Tao; Wang Chengzhi; Zhang Pan; Peng Rui; Mu Jinglan; et al. (Chemical Engineering Journal, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

The Spatial–Temporal Characteristics of Wave Energy Resource Availability in the China Seas - Rui-Zhe Shen; Cheng-Tao Yi; Yu-Nuo Liu; Lei Wang; Kai Wu; Mu-Yu Chen; Chong-Wei Zheng (Journal of Marine Science and Engineering, 2025)
For coastal nations and regions, wave energy provides a localized energy solution, decreasing dependency on external energy sources and fostering the sustainable development of local economies. Effective wave height occurrence (EWHO) represents the availability of wave energy and is a crucial parameter for site selection for optimal wave energy. This paper systematically analyzes the distribution of EWHO in China seas areas using significant wave height (SWH) data in the fifth generation of ECMWF atmospheric reanalysis (ERA5) and key climate indices. Employing methods such as climate statistical analysis, linear regression, significance testing, and trend analysis, the study highlights the temporal and spatial distribution characteristics, variation trends, and correlations with climate indices of EWHO. This research aims to provide technical assistance and decision support for the development of wave energy at sea. The results indicate the following conclusions: (1) The high EWHO in the China seas is predominantly located in northern Nanhai, southern Donghai, and the eastern waters of the Philippine Islands. The EWHO is highest in winter. (2) The growth trend of EWHO is most notable in the sea area east of the line connecting the Ryukyu Islands, Taiwan, and the northeastern Philippines, peaking in spring and being relatively weak in winter. (3) The correlation between NINO3 and EWHO is most significant in Nanhai and the northeastern waters of the Philippines, peaking in February with correlation coefficients ranging from −0.30 to −0.50.

Downregulation of HSPB1 and MGST1 Promotes Ferroptosis and Impacts Immune Infiltration in Diabetic Cardiomyopathy - Yaoli Xie; Bin Liang; Zhijun Meng; Rui Guo; Caihong Liu; Yi Yuan; Wei Mu; Yajing Wang; Jimin Cao (Cardiovascular Toxicology, 2025)

Barrierless reactions of C2 Criegee intermediates with H2SO4 and their implication to oligomers and new particle formation - Yang Cheng; Chao Ding; Tianlei Zhang; Rui Wang; Ruxue Mu; Zeyao Li; Rongrong Li; Juan Shi; Chongqin Zhu (Journal of Environmental Sciences, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Hyperspectral image classification based on faster residual multi-branch spiking neural network - Yahui Li; Yang Liu; Rui Li; Liming Zhou; Lanxue Dang; Huiyu Mu; Qiang Ge (Computers & Geosciences, 2025)

Enhancing thermal conductivity, electromagnetic interference shielding, and joule heating in polyether ether ketone composites using three-dimensional scaly carbon fibre structures and structural optimisation - Yifan Wang; Fengyu Wen; Yashu He; Lin Cheng; Haoyuan Tan; Jierun Ma; Pengbo Lian; Yuxuan Gu; Rui Chen; Jianxin Mu (Chemical Engineering Journal, 2025)

Enhanced electrochemical performance of NCM811-based batteries by using a multifunctional electrolyte additive - Aijia Wei; Shuxing Mei; Jinping Mu; Peng Liu; Xue Bai; Rui He; Xiaohui Li; Yuxin Niu; Lihui Zhang; Zhenfa Liu; Lei Wang (Chemical Engineering Journal, 2025)

Geosites Associated with Paleovolcanic Landscapes and Paleontology in Hoboksar Mongol Autonomous County, Xinjiang Uygur Autonomous Region, NW China - Hong-Xu Mu; Qing-Wei Song; Jun-Ting Qiu; Long-Xin Xu; Xin-Min Rui (Geoheritage, 2025)

Synchronous monitoring agricultural water qualities and greenhouse gas emissions based on low-cost Internet of Things and intelligent algorithms - Huazhan Zhang; Rui Ren; Xiang Gao; Housheng Wang; Wei Jiang; Xiaosan Jiang; Zhaofu Li; Jianjun Pan; Jinyang Wang; Songhan Wang; Yanfeng Ding; Yue Mu; et al. (Water Research, 2025)

Regulation of oxygen vacancy by in-situ piezoelectric synthesized BiVO4 to induce spin polarization for boosting the piezo-photocatalytic activity - Ying Cheng; Tao Yu; Xuefei Lei; Biao Wang; Wenning Mu; Xuanwen Liu; Rui Guo (Chemical Engineering Journal, 2025)

In-situ electrogenerated persulfate activated by co-existing Cu(II) for sustainable removal of sulfonamides from environmental waters - Yusheng Zhou; Yongfei Ma; Zhikang Deng; Chenyu Zeng; Rui Mu; Yifan Liu; Zulin Zhang (Journal of Environmental Chemical Engineering, 2024)

Detection of ultra-low concentration NH3, SO2, and NO using UV-DOAS combined with multidimensional spectral fusion - Fei Xie; Yongqi Wu; Jie Gao; Mu Li; Rui Zhu; Xijun Wu; Yungang Zhang (Fuel, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

Tracking the impact of typhoons on maize growth and recovery using Sentinel-1 and Sentinel-2 data: A case study of Northeast China - Yongling Mu; Shengbo Chen; Yijing Cao; Bingxue Zhu; Anzhen Li; Liang Cui; Rui Dai; Qinghong Zeng (Agricultural and Forest Meteorology, 2024)

Biogeography of a Global Plant Invader: From the Evolutionary History to Future Distributions - Lei Zhang; Isolde van Riemsdijk; Mu Liu; Zhiyong Liao; Armand Cavé‐Radet; Jingwen Bi; Shengyu Wang; Yujie Zhao; Peipei Cao; Madalin Parepa; Oliver Bossdorf; Armel Salmon; et al. (Global Change Biology, 2024)
Biological invasions pose a global challenge, affecting ecosystems worldwide and human societies. Knowledge of the evolutionary history of invasive species is critical to understanding their current invasion success and projecting their future spread. However, to date, few studies have addressed the evolutionary history and potential future spread of invaders simultaneously. In this study, we explored both evolutionary history and spatiotemporal dynamic patterns of the distribution of Reynoutria japonica , known as one of the world's worst plant invaders. We analysed 265 R. japonica samples from its current geographical ranges across three continents, using seven chloroplast DNA (cpDNA) markers to establish the phylogenetic relationships among extant populations. We combined these with ecological niche modelling to infer historical and more recent migration patterns and predict potential future distribution changes under climate change. Our results indicate that climate fluctuations and sea level changes likely facilitated the expansion of R. japonica from southern Japan to continental East Asia in the Pliocene, followed by a contraction in East Asian populations. In the recent Holocene, human activities have then enabled a linage of this species to spread from Japan to Europe and North America, resulting in three major global clades. Future climate scenarios suggest a northward expansion of R. japonica in Europe and North America, but shrinking habitat in China. Our study, thus, demonstrates the complex influences of historical climate‐driven migrations, human activities and future climate changes on the global distribution of an invasive species.

Smart nanoscale lamellated supramolecular assemblies overcome biofilm barriers and enhance foliar affinity for efficient control of bacterial diseases - Lizhu Xiang; Xiaohui Wang; Jinghan Yang; Rui Wang; Lin Chen; Xiaoping Bao; Xianfu Mu; Peiyi Wang (Chemical Engineering Journal, 2024)

Functionally-designed metal salt and ball milling co-modified sludge biochar for adsorptive removal of trace level sulfamethoxazole: Behavior, characterization, mechanism and DFT study - Rui Mu; Shufang Qian; Yongfei Ma; Zhikang Deng; Jiayi Tang; Zulin Zhang (Journal of Environmental Chemical Engineering, 2024)

Ferrate (VI) oxidation of sulfamethoxazole enhanced by magnetized sludge-based biochar: Active sites regulation and degradation mechanism analysis - Zhikang Deng; Yongfei Ma; Jinyao Zhu; Chenyu Zeng; Rui Mu; Zulin Zhang (Environmental Pollution, 2024)

In situ activation of peroxymonosulfate with bioelectricity for sulfamethoxazole sustainable removal - Zhikang Deng; Yongfei Ma; Jinyao Zhu; Chenyu Zeng; Rui Mu; Zulin Zhang (Environmental Research, 2024)

Efficient degradation of sulfadiazine by UV-triggered electron transfer on oxalic acid-functionalized corn straw biochar for activating peroxyacetic acid: Performance, mechanism, and theoretical calculation - Chenyu Zeng; Yongfei Ma; Ping Li; Xi Chen; Hongtao Liu; Zhikang Deng; Rui Mu; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Radical/non-radicals oxidative degradation of sulfamethoxazole via peroxymonosulfate activation by ball milling and N-doping co-functionalized sludge biochar - Rui Mu; Yongfei Ma; Yongzhen Ding; Chenyu Zeng; Xi Chen; Jinyao Zhu; Zhikang Deng; Zulin Zhang (Journal of Water Process Engineering, 2024)

The preparation of synbiotic AHY relieving loperamide-induced constipation and its modulation mechanism in vivo - Lai Jiang; Rui Zhang; Xudong Lin; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Social determinants of health and their relation to suboptimal health status in the context of 3PM: a latent profile analysis - Lai Kun Tong; Yue Yi Li; Yong Bing Liu; Mu Rui Zheng; Guang Lei Fu; Mio Leng Au (EPMA Journal, 2024)

Facile synthesis of ball-milling and oxalic acid co-modified sludge biochar to efficiently activate peroxymonosulfate for sulfamethoxazole degradation: 1O2 and surface-bound radicals - Xi Chen; Jinyao Zhu; Yongfei Ma; Chenyu Zeng; Rui Mu; Zhikang Deng; Zulin Zhang (Journal of Hazardous Materials, 2024)

Highly efficient activation of ferrate (VI) via corncob biochar assisted by electrochemistry for the removal of sulfamethoxazole from water - Zhikang Deng; Jinyao Zhu; Chenyu Zeng; Rui Mu; Yongfei Ma; Zulin Zhang (Chemical Engineering Journal, 2024)

The Relationships Between Danxia Geoheritages and Regional Tectonics in Southern Sichuan Basin: Implications for the Spatial Distribution of Danxia Landforms in China - Jun-Ting Qiu; Hong-Xu Mu; Xin-Min Rui; Yan-Jie Yang; Pengju Li; Liang Qiu; Chao-Bin Xu (Geoheritage, 2024)

Capturing spatiotemporal heterogeneity in fertilizer application for better modelling paddy water nitrogen and phosphorus pollution at regional scale - Rui Ren; Huazhan Zhang; Xiang Gao; Housheng Wang; Wei Jiang; Yuhui Wang; Xiaosan Jiang; Zhaofu Li; Haiyan Zhao; Ganghua Li; Yanfeng Ding; Yue Mu (Agriculture, Ecosystems & Environment, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

Non-radical mediated reduced graphene oxide/polypyrrole catalytic ceramic membrane-PDS system for source control of SMX - Rui Wang; Hong You; Zhipeng Li; Jing Zhao; Mu Li; Jing Zhu; Guoyu Zhang; Xianshi Wang; Haoran Leng; Shaojie Qi; Binghan Xie (Chemical Engineering Journal, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Oxalic acid-enhanced sulfamethoxazole degradation by V2O3/percarbonate process: Insights into the reactive oxygen species generation and conversion - Rui Liu; Mu-cheng Xu; Jin-yan Yang (Chemical Engineering Journal, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Review on fault-tolerant control of unmanned underwater vehicles - Fuqiang Liu; Zuxing Ma; Bingxian Mu; Chaoqun Duan; Rui Chen; Yi Qin; Huayan Pu; Jun Luo (Ocean Engineering, 2023)

The molecular basis of heat stress responses in plants - Yi Kan; Xiao-Rui Mu; Jin Gao; Hong-Xuan Lin; Youshun Lin (Molecular Plant, 2023)

PANI grafted onto waste poros polyurethane for co-adsorption of multiple pollutants in industrial wastewater - Ning Wang; Yirui Guo; Yi Song; Wei Yan; Xuesong Gong; Yunfeng Li; Rui hua Mu; Yonghong Liu; Luohong Zhang (Journal of Water Process Engineering, 2023)

Prenatal PM2.5 exposure increases the risk of adverse pregnancy outcomes: evidence from meta-analysis of cohort studies - Wanrong Wang; Siqi Mu; Weizhen Yan; Naiyu Ke; Han Cheng; Rui Ding (Environmental Science and Pollution Research, 2023)

Global prevalence and factors affecting the level of Cryptosporidium contamination in soil: A systematic review, meta-analysis, and meta-regression - Mu-Ran Zuo; Xiao-Ting Li; Rui-Zhe Xu; Wen-Chao Sun; Hany M. Elsheikha; Wei Cong (Science of The Total Environment, 2023)

Machine learning improves prediction of severity and outcomes of acute pancreatitis: a prospective multi-center cohort study - Jia-Ning Li; Dong Mu; Shi-Cheng Zheng; Wei Tian; Zuo-Yan Wu; Jie Meng; Rui-Feng Wang; Tian-Lei Zheng; Yue-Lun Zhang; John Windsor; Guo-Tao Lu; Dong Wu (Science China Life Sciences, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Mechanistic insights into dissolved organic matter-driven protistan and bacterial community dynamics influenced by vegetation restoration - Zhang-mu Jing; Qing-qian Li; Yan-jie Wei; Bin Dong; Peng Yuan; Rui-xia Liu; Hong-jie Gao (Environmental Research, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Silencing P25, HC-Pro and Brp1 of Potato Virus (Viroid) Using Artificial microRNA Confers Resistance to PVX, PVY and PSTVd in Transgenic Potato - Lili Jiang; Rui Mu; Ziquan Wang; Shangwu Liu; Dianqiu Lu (Potato Research, 2023)

Predictive and estimation model of Cd, Ni, and Zn bioaccumulations in maize based on diffusive gradients in thin films - Rui Chen; Xiulin Mu; Jiaxing Liu; Nuo Cheng; Rongguang Shi; Miaomiao Hu; Zhuoran Chen; Hao Wang (Science of The Total Environment, 2023)

Simulation of integrated anaerobic digestion-gasification systems using machine learning models - Yadong Ge; Junyu Tao; Zhi Wang; Chao Chen; Rui Liang; Lan Mu; Haihua Ruan; Yakelin Rodríguez Yon; Beibei Yan; Guanyi Chen (Bioresource Technology, 2023)

Mobilization of water affecting formation and dissociation of hydrate in clay sediment - Peng Zhang; Xueping Chen; Lianhai Zhang; Shuaijun Li; Wenting Chen; Qingbai Wu; Shuanshi Fan; Rui Bao; Cuicui Mu (Chemical Engineering Journal, 2023)

Balance the rapid release of insecticide microcapsules using double-layer shielding effect when the foliar application - Rui Wang; Song Liu; Feng-shou Sun; Xin Yu; Xiao Liu; Bei-xing Li; Wei Mu; Da-xia Zhang; Feng Liu (Chemical Engineering Journal, 2023)

Sensor Partitioning Placements via Random Walk and Water Quality and Leakage Detection Models within Water Distribution Systems - Tianwei Mu; Manhong Huang; Shi Tang; Rui Zhang; Gang Chen; Baiyi Jiang (Water Resources Management, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Evaluating the stability of Outang landslide in the Three Gorges Reservoir area considering the mechanical behavior with large deformation of the slip zone - Junbiao Yan; Zongxing Zou; Rui Mu; Xinli Hu; Jincheng Zhang; Wen Zhang; Aijun Su; Jinge Wang; Tao Luo (Natural Hazards, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Two new diterpenoids with their antiproliferative activities from the supercritical fluid extraction of Croton crassifolius root - Chao Liu; Rui-rui Zhang; Qing-lin Niu; Jing Zhang; Mu-xuan Wang; Na-na Meng; Qing Wang; Jin-yue Sun; Wen-liang Wang (Natural Product Research, 2021)

Alkalibacillus aidingensis sp. nov., an Bacterium Isolated from Aiding Lake in Xinjiang Province, North-West China - Rui Li; Li Yang; Rüdiger Pukall; Meina Neumann-Schaal; Chang-Gai Mu; Yong-Jiang Shi; Yun Wang; Gang-Qiang Jiang; Yu-Guang Zhou; Man Cai; Min Yin; Wen-Yong Zhu; et al. (Current Microbiology, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Pseudomonas aeruginosa antitoxin HigA functions as a diverse regulatory factor by recognizing specific pseudopalindromic DNA motifs - Yingjie Song; Guihua Luo; Yibo Zhu; Tao Li; Changcheng Li; Lihui He; Ninglin Zhao; Chang Zhao; Jing Yang; Qin Huang; Xingyu Mu; Xinyue Tang; et al. (Environmental Microbiology, 2021)
Summary Type II toxin‐antitoxin (TA) systems modulate many essential cellular processes in prokaryotic organisms. Recent studies indicate certain type II antitoxins also transcriptionally regulate other genes, besides neutralizing toxin activity. Herein, we investigated the diverse transcriptional repression properties of type II TA antitoxin PaHigA from Pseudomonas aeruginosa . Biochemical and functional analyses showed that PaHigA recognized variable pseudopalindromic DNA sequences and repressed expression of multiple genes. Furthermore, we presented high resolution structures of apo‐PaHigA, PaHigA‐P higBA and PaHigA‐P pa2440 complex, describing how the rearrangements of the HTH domain accounted for the different DNA‐binding patterns among HigA homologues. Moreover, we demonstrated that the N‐terminal loop motion of PaHigA was associated with its apo and DNA‐bound states, reflecting a switch mechanism regulating HigA antitoxin function. Collectively, this work extends our understanding of how the PaHigB/HigA system regulates multiple metabolic pathways to balance the growth and stress response in P. aeruginosa and could guide further development of anti‐TA oriented strategies for pathogen treatment.

Isolation and molecular characterization of bovine herpesvirus 4 from cattle in mainland China - Jun Lin; Rui-Hong Chen; Mu-Jiao Yang; Yuan-Mao Zhu; Fei Xue (Archives of Virology, 2021)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Isolation and synthesis of a new benzylated alkamide from the roots of Lepidium meyenii - Yan-Qing Ye; Zu-Hong Ma; Qiao-Fen Yang; Yan-Qi Sun; Rui-Qi Zhang; Run-Fang Wu; Xin Ren; Li-Juan Mu; Zhi-Yong Jiang; Min Zhou (Natural Product Research, 2019)

Poly-PR in C9ORF72-Related Amyotrophic Lateral Sclerosis/Frontotemporal Dementia Causes Neurotoxicity by Clathrin-Dependent Endocytosis - Rui Wang; Xingyun Xu; Zongbing Hao; Shun Zhang; Dan Wu; Hongyang Sun; Chenchen Mu; Haigang Ren; Guanghui Wang (Neuroscience Bulletin, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Evaluation of pulsed corona discharge plasma for the treatment of petroleum-contaminated soil - Rui Li; Yanan Liu; Ruiwen Mu; Wenyan Cheng; Stéphanie Ognier (Environmental Science and Pollution Research, 2017)

Effects of light curing modes and ethanol-wet bonding on dentin bonding properties - Mu-zi Li; Jin-rui Wang; Hong Liu; Xia Wang; Kang Gan; Xiu-ju Liu; De-li Niu; Xiao-qing Song (Journal of Zhejiang University-SCIENCE B, 2016)

A novel surfactant-, NaCl-, and protease-tolerant β-mannanase from Bacillus sp. HJ14 - Rui Zhang; Zhifeng Song; Qian Wu; Junpei Zhou; Junjun Li; Yuelin Mu; Xianghua Tang; Bo Xu; Junmei Ding; Shucan Deng; Zunxi Huang (Folia Microbiologica, 2016)

Degradation of p-Nitrophenol in Soil by Dielectric Barrier Discharge Plasma - Rui Li; Yanan Liu; Yu Sun; Wenjuan Zhang; Ruiwen Mu; Xiang Li; Hong Chen; Pin Gao; Gang Xue; Stephanie Ognier (Water, Air, & Soil Pollution, 2015)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Molecular characterization of Chinese Hop stunt viroid isolates reveals a new phylogenetic group and possible cross transmission between grapevine and stone fruits - Zhixiang Zhang; Ying Zhou; Rui Guo; Lingxiao Mu; Yuanai Yang; Shifang Li; Hongqing Wang (European Journal of Plant Pathology, 2012)

Expression and characterization of Momordica Chanrantia anti-hyperglycaemic peptide in Escherichia coli - Si-Xiu Liu; Zhong-Ping Fu; Rui-Min Mu; Zhi-Bi Hu; Fu-Jun Wang; Xiang-Rong Wang (Molecular Biology Reports, 2010)

Trend and change-point analyses of streamflow and sediment discharge in the Yellow River during 1950–2005 - Peng Gao; Xunchang Zhang; Xinming Mu; Fei Wang; Rui Li; Xiaoping Zhang (Hydrological Sciences Journal, 2010)

Seasonal morphological and biochemical changes of Dahlgren cells implies a potential role of the caudal neurosecretory system (CNSS) in the reproduction cycle of teleostean fish - Heng Chen; Rui Mu (Fish Physiology and Biochemistry, 2008)

A Study of Conservation Genetics in Cupressus chengiana, an Endangered Endemic of China, Using ISSR Markers - Bingqing Hao; Wang Li; Mu Linchun; Yao Li; Zhang Rui; Tang Mingxia; Bao Weikai (Biochemical Genetics, 2006)